Enhancing water sustainability in the Gobi Desert: processes based on IWRM principles - Bolormaa Purevjav; Bern Klein; Julian Dierkes; Nadja Kunz; André Xavier; Suzette McFaul (Discover Water)
Abstract The mining industry is an important sector that contributes to economic growth and employment creation in Mongolia. Water access, water quality, and community engagement are the major challenges the Mongolian mining industry faces. Integrated Water Resource Management (IWRM) is a holistic water management approach that applies principles of economic efficiency, social equity, and environmental sustainability to ensure water sustainability. A research study was carried out to understand stakeholders’ views and perspectives on IWRM and to identify water use practices, challenges, and barriers in the Gobi Desert mining region. The aim was to identify processes that help to improve access to water in the Gobi Desert region. This research applied a qualitative approach and employed three data collection methods: (1) semi-structured interviews; (2) field observations and (3) documents and academic articles reviews. Research participants were representatives from mining companies, local communities, government, and river basin administrations. In the Gobi Desert region, processes contributing to improving water management are: (1) participatory water monitoring, (2) coal processing plant educational visits, (3) local stakeholders council’s meetings, (4) herder’s well improvement projects, (5) independent water auditing, and (6) water advocacy events. These practices, aligned with the core principles of IWRM provide practical solutions for sustainable water management in mining regions, with the potential for global adaptation.